Exploration of homodimer receptor: homodimer protein interactions. (29th July 2009) - Vera, Julio; Kwon, Taesoo; Schmitz, Ulf; Kolch, Walter; , Olaf Wolkenhauer
Homodimerisation is producing a protein?protein complex composed of two identical molecules. Dimerisation is a phenomenon often occurring in the regulation of biochemical systems like signal transduction pathways. We investigated whether the existence of a homodimer-activated receptor and the activation of homodimer transducers correspond to a more general pattern in cell signalling. We developed a workflow to merge data from the Gene Ontology and the BIND database to produce a list of interactions between homodimer receptors and homodimer proteins. Finally, we found a prevalence of homodimer?homodimer interactions in signalling systems in human cells.